Linear IgA disease: the IgA and IgG response to dermal antigens demonstrates a chiefly IgA response to LAD285 and a dermal 180-kDa protein. - Allen, J; Wojnarowska, F (2003)
BACKGROUND: Linear IgA disease (LAD) of adults and children is mediated by IgA antibodies that target proteins of the epithelial adhesion complex. Most studies have concentrated on the epidermal-associated antigens; the dermal antigens remain unresolved. OBJECTIVES: To determine the dermal antigen repertoire of IgA and IgG antibodies in LAD. METHODS: Immunoblotting was carried out on salt-split and urea-extracted dermal skin extracts with IgA antibodies (63 adult and 34 childhood sera) and with IgG antibodies (49 adult and 18 childhood sera). RESULTS: Antigens were identified by IgA (61%), IgG (27%) and by both antibody isotypes (19%). LAD285 and an antigen of 180 kDa were the major dermal antigens identified, and antigens of 230 kDa, collagen VII and a protein under 100 kDa were identified less commonly. IgA autoantibodies from adults bound single antigens more frequently than multiple antigens; from children they bound single and multiple antigens equally. The binding of multiple antigens was, however, more common in children than adults. The IgG response was weaker. The 180-kDa antigen was the main IgG dermal target, and with a single exception, IgG autoantibodies targeted single antigens. CONCLUSIONS: There was an IgA and IgG response to dermal antigens in LAD; however, the dual antibody response was limited. The antibody response to LAD285 and a 180-kDa antigen (probably BP180) suggests that intermolecular epitope spreading of the antigens associated with the extracellular matrix/dermal components of the basement membrane contributes to the immunopathology of the disease. The restricted IgG response suggests that dermal-binding IgG autoantibodies are not pathologically significant.